Regulation of CD8+ T Cells and Antitumor Immunity by Notch Signaling - Tsukumo, Shin-ichi; Yasutomo, Koji (Frontiers in Immunology, 2018)
Cancer immunosurveillance is critical for the elimination of neoplastic cells. In addition, recent advances in immunological checkpoint blockade drugs have revealed the importance of the immune system in cancer treatment. As a component of the immune system, CD8+ T cells have important roles in suppressing tumors. CD8+ T cells can kill tumor cells with cytotoxic molecules, such as granzymes and perforin. IFN gamma which is produced by CD8+ T cells, can increase the expression of MHC class I antigens by tumor cells, thereby rendering them better targets for CD8+ T cells. IFNγ also has crucial functions in enhancing the anti-tumor abilities of other immune cells. Therefore, it has been hypothesized that anti-tumor immunity could be improved by modulating the activity of CD8+ T cells. The Notch pathway regulates CD8+ T cells in multiple ways. It directly upregulates mRNA expression of granzyme B and perforin, enhances differentiation toward short-lived effector cells, and maintains memory T cells. Intriguingly, CD8+ T cell-specific Notch2 deletion impairs anti-tumor immunity, whereas the stimulation of the Notch pathway can increase tumor suppression. In this review, we will summarize the roles of the Notch pathway in CD8+ T cells and discuss issues and implications for its use in anti-tumor immunity